The Nexus between Agricultural Education Curriculum and Food Security in Nigeria: Challenges and Way Forward for Sustainable Practice - Osagiede, Mercy Afe (NIU Journal of Educational Research, 2024)
This essay investigates the connection between Nigerian food security and agricultural education curricula. The study explores the importance of incorporating agricultural education within the formal education system with an emphasis on Nigeria in order to address the urgent problems of food insecurity in the nation. It looks at how agricultural education can help people acquire the information, abilities, and mindset needed to increase agricultural output, support sustainable farming methods, and guarantee that every Nigerian has access to wholesome food. In addition to discussing policy implications and reform strategies aimed at strengthening the relationship between agricultural education and food security in Nigeria, the paper emphasises the significance of fostering innovation and entrepreneurship in the agricultural sector, promoting practical training and experiential learning, and aligning curriculum with industry needs. These strategies include investing in vocational and technical education, youth empowerment programmes, and agricultural extension services. The paper offers insights into how Nigeria might leverage the transformative potential of agricultural education to achieve food security, support rural development, and create a more resilient and sustainable food system by examining successful initiatives and best practices. Overall, the study emphasises how crucial agricultural education curricula are to tackling issues with food security and promoting agricultural growth in Nigeria. Keywords: Agricultural Education, Food Security, Curriculum, Curriculum Integration, Sustainable Agriculture